Pengaruh Label Halal, Brand Image dan Kualitas Pelayanan Terhadap Keputusan Pembelian di BFC 45 Prabumulih - Ilyas, Mudzakir; Putri, Rika Rahmadina; Fitri, Nadiatul Karimah (Assyarikah: Journal of Islamic Economic Business, 2024)
This study aims to determine how the influence of halal labeling, brand image, and service quality on purchasing decisions at BFC 45 Prabumulih. With halal labeling variables, brand image, and service quality which are independent variables in this study and purchasing decisions as dependent variables and can be a reference in improving the quality of BFC 45 Prabumulih. This study uses a quantitative research design with a questionnaire as a data collection tool, using purposive sampling technique with a total of 92 respondents who fall into the characteristics of the respondents. The types of data used are secondary and primary data and the data analysis techniques used are instrument tests, classical assumption tests, multiple linear regression analysis tests and hypothesis testing. Based on the results of data processing that has been done, this study shows the results that halal labeling, brand image partially affect purchasing decisions at BFC 45 Prabumulih, while service quality partially has no effect on purchasing decisions at BFC 45 Prabumulih and simultaneously halal labeling, brand image and service quality affect purchasing decisions.